Konsep Persatuan Bangsa dalam Piagam Madinah dengan Konstitusi Indonesia - Aziza Aziz Rahmaningsih (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The wealth of a country is reflected in its ethnicity, religion and culture. This fact of diversity can be seen in the city of Medina which has several types of groups that have been regulated in a constitution known as the Medina Charter. The Medina Charter is a written evidence of politics made by the Prophet Muhammad to regulate life together in Medina which is inhabited by various culture. Indonesia is dominated by a pluralistic people of different ethnicities, refional languages, customs and regilions. Thus, the national unity of the 1945 Medina Charter and the Constitution of the Republic of Indonesia is equalized by uniting the people of a country and empowering the community and its people according to their beliefs. Meanwhile, the Medina Charter and the 1945 Constitution have differences, where in the Medina Charter explicitly the unity is based on religious unity, and in the 1945 Constitution there is no explicit classification.